Reflexive Inquiry’s Impact on Mindful Teaching for Student Wellbeing (LEARNing Landscapes, 2024)
This inquiry investigates the effects of trauma on students by analyzing personal experiences and teaching methods. Through the lens of autoethnography, a nonfictional storytelling approach, I reflect on my learning journey to identify compassionate and mindful teaching practices, aiming to foster a trauma‑sensitive classroom environment. Emphasizing the significance of teachers sharing their stories through autoethnography, this exploration contributes valuable insights to the ongoing discourse on trauma-informed pedagogy for student wellbeing.
Keywords: wellbeing; trauma-sensitive education; grief; resilience